INTERACTION OF BIORESORBABLE COMPOSITE IMPLANTS MADE BY SOLUTION BLOW SPINNING WITH TISSUES - D. E. Kulbakin; E. L. Choynzonov; N. V. Cherdyntseva; E. N. Bolbasov; V. A. Svetlichnyi; I. N. Lapin; S. I. Tverdokhlebov; A. A. Zheravin; L. N. Bondar; V. N. Perelmuter (Сибирский научный медицинский журнал)
This work represents the results of the study of the surrounding tissues reaction to the implantation of bioresorbable implants formed by the solution blow spinning from polylactic acid and ultrafine calcium phosphate powders, depending on the time and place of implantation. Using scanning electron microscopy it is shown that implants formed from randomly interwoven fibers have interconnected open porosity. It was established that the addition of calcium phosphate ultrafine powders does not cause changes in the formed implants structure. Histological investigation of tissue specimens from the implantation site revealed a high ability of created implants to successful integration with surrounding tissue after 15 days from the moment of implantation. Complete or partial implant resorption with substitution by own tissues was registered at 90 days after implantation. It was established that implantation of composite bioresorbable implants on the ilium bone stimulates the osteogenic process better than the implantation on skull bone within the same period. It was defined that scarification of the outer cortical plate in implant contact points with bone tissue increases the implants ability to stimulate osteogenic process. It was shown that the composite implants filled with calcium phosphate dibasic dehydrate in ultrafine powder form have the largest ability to stimulate osteogenesis.